Changes in vascular reactivity and endothelial Ca2+ dynamics with chronic low flow. (April 2017) - Taylor, Mark S.; Choi, Chung‐sik; Bayazid, Leith; Glosemeyer, Katherine E.; Baker, Calvin C. P.; Weber, David S.
Abstract: Disruption of blood flow promotes endothelial dysfunction and predisposes vessels to remodeling and atherosclerosis. Recent findings suggest that spatial and temporal tuning of local Ca 2+ signals along the endothelium is vital to vascular function. In this study, we examined whether chronic flow disruption causes alteration of dynamic endothelial Ca 2+ signal patterning associated with changes in vascular structure and function. For these studies, we performed surgical PL of the left carotid arteries of mice to establish chronic low flow for 2 weeks; right carotid arteries remained open and served as controls (C). Histological sections showed substantial remodeling of PL compared to C arteries, including formation of neointima. Isometric force measurements revealed increased PE‐induced contractions and decreased KCl‐induced contractions in PL vs C arteries. Endothelium‐dependent vasorelaxation in response to ACh; 10 −8 to 10 −5 mol/L) was significantly impaired in PL vs C vessels. Evaluation of endothelial Ca 2+ using confocal imaging and custom analysis exposed distinct impairment of Ca 2+ dynamics in PL arteries, characterized by reduction in active sites and truncation of events, corresponding to attenuated vasorelaxation. Our findings suggest that endothelial dysfunction in developing vascular disease may be characterized by distinct shifts in the spatial and temporal patterns of localized Ca 2+ signals.